Transition, special moratorium issue - Watts, Steve, editor; ASCSU, publisher (Colorado State University. Libraries, 1969)
October 14 special issue of the Transition, a weekly Colorado State University student newspaper and an alternative to the Rocky Mountain Collegian. Includes articles, photographs, and illustrations concerning the Moratorium to End the War in Vietnam, a national anti-war demonstration, held October 15, 1969.
Transition
Keywords: Colorado State University -- Periodicals; Fort Collins (Colo.) -- Periodicals